Role Essential Oils In Hair Growth - Cherry Chalik; Rina Gustia (Jurnal Ners, 2025)
The use of essential oils has begus to be in great demand in the community, both for health purposes and in cosmetic ingredients. Essential oils are natural active ingredients containing various growt hcomplex chemical components and unique compounds. Several studies have begun to research the benefits of the bioactive ingredients in essential oils on hair growth. The benefits of essential oils that have begun researched are the stimulating effect of the hair growth. The existence of various components and active ingredients in essential oils requires further studies regarding the mechanism of action and how essential works in growing hair.